A study on the development of the Malaysian debt market / Lee Meng Wai - Lee , Meng Wai (2019)
Bond markets are an integral part of a country’s capital market and together with the banking sector represent components of the financial system of the country. This study looked at development of the Malaysian debt market, which covered the domestic bond market and banking sector. The study covered the early years when the government began to develop the private domestic bond market to complement the already established government bond market. It also spanned the important periods for the domestic bond market. First, when there was greater activity to access the bond market to raise funds for economic recovery and bank recapitalization following the 1997-98 Asian financial crisis. Subsequently, the years when there was a flurry of government measures to boost the domestic bond market and diversify risks from the banking sector, thus adding breadth and depth to Malaysia’s financial system. This study analyzed the impact from various macroeconomic factors as well as impacts of the major financial crises on the Malaysian domestic bond market, banking sector and private financing. The study found that development of the Malaysian domestic bond market has to contend with competition from the country’s dominant banking sector and, to a lesser extent, the popular equity market. In fact, it was found during the study period, the bank concentration ratio, which measured the market share and, accordingly, concentration of power in the country’s top banks, seemed to exert a greater impact on development of the domestic bond market than the size of the banking sector per se. This study also analyzed how the persistent and sizeable fiscal deficits in Malaysia since 1998 have affected the domestic bond market, especially the private bond market. The study found that development of the domestic government bond market and the trend in the country’s fiscal balances have been instrumental in boosting the private domestic bond market. In fact, the size of the domestic government bond market was even more influential than government debt in boosting the development of this segment. Hence, further developing the government bond market will contribute to domestic bond market development and should be given higher priority by the Malaysian authorities. Instability in the Ringgit negatively impacted the domestic bond market. The study also found that the local banking sector was negatively affected by the bank concentration ratio and higher spreads in interest rates, but growth in government debt had a positive impact on bank loans. Meanwhile, private financing, comprising bank loans and corporate bonds, was positively associated with government debt and the local equity market, but negatively impacted by instability in the Ringgit. It is hoped that the findings in this study would be helpful as input to future government policy design and more embracive policies to further develop and / or reform the financial markets, including the domestic bond market. That is, the study findings can be relevant to Malaysia and other developing countries.